2005
DOI: 10.1021/ma0490606
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Surface Crystallization in Thin Films of Poly(ethylene terephthalate)

Abstract: In-situ grazing incidence X-ray diffraction has been used to investigate the kinetics of crystallization at the surface of thin films of poly(ethylene terephthalate) (PET). By varying the angle of incidence of the X-ray beam around the critical angle of the film, the penetration depth can be tuned to allow a direct comparison of molecular ordering in the surface and bulk of the film. The results show that ordering occurs significantly faster at the surface in the temperature range 90−100 °C (close to the bulk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 25 publications
4
56
0
Order By: Relevance
“…A high degree of crystallisation is known to increase the tensile yield stress (hence shear yield stress) of PET [33] and may also encourage strain hardening of the polymer. No elevated yield stress or strain hardening in the saturation regime (10-15% tensile strain) is observed for the HS PET film during tensile testing but this is probably due to the localisation of the increased crystallinity at the surface of the film, as reported in the literature [31,32]. It appears that the crystalline surface morphology caused by heat treatment strengthens the polymer in the interfacial region allowing a superior τ ⁎ to be observed that matches that of PEN.…”
Section: Adhesive Strengthsupporting
confidence: 49%
See 1 more Smart Citation
“…A high degree of crystallisation is known to increase the tensile yield stress (hence shear yield stress) of PET [33] and may also encourage strain hardening of the polymer. No elevated yield stress or strain hardening in the saturation regime (10-15% tensile strain) is observed for the HS PET film during tensile testing but this is probably due to the localisation of the increased crystallinity at the surface of the film, as reported in the literature [31,32]. It appears that the crystalline surface morphology caused by heat treatment strengthens the polymer in the interfacial region allowing a superior τ ⁎ to be observed that matches that of PEN.…”
Section: Adhesive Strengthsupporting
confidence: 49%
“…This relaxed amorphous phase is then responsible for the lower modulus and yield stress as it must be reoriented under tension. The very high crystallinity observed at the surface by AFM is probably due to the fact that the T g is lower at the surface leading to a higher degree of crystallisation there than in the bulk [31,32]. Finally, as expected, PEN exhibits a greater modulus and yield stress.…”
Section: Substrate Propertiesmentioning
confidence: 55%
“…In other materials systems, this behavior is often explained by the presence of disordered interface regions, which account for an increasing portion of the film as the overall thickness decreases. [28][29][30] In our case, crystallization is more FULL PAPERS complicated: the semiconductor/dielectric interface is host not only to disordered material but also to interfacenucleated crystalline domains.…”
Section: Resultsmentioning
confidence: 85%
“…In fact, it is found from many studies on the crystallization behavior that the crystallinity of block chains confined in nanolamellae increases sigmoidally with a finite induction time, indicating that the crystallization is virtually driven by a combined mechanism of heterogeneous nucleation and subsequent crystal growth. Because a comprehensive understanding of the detailed crystallization mechanism of homopolymers confined in nanolamellae is directly applicable to the surface crystallization of homopolymers [88][89][90][91][92] or crystallization within thin films [93][94][95][96][97][98], it is essential to examine the crystallization of homopolymers (and also block chains) confined in various nanolamellae.…”
Section: Nanolamellaementioning
confidence: 99%